TỶ LỆ GIỚI TÍNH ỐC BƯƠU ĐỒNG (Pila polita Deshayes, 1830) Ở ĐỒNG BẰNG SÔNG CỬU LONG - Lê, Văn Bình; Ngô, Thị Thu Thảo (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
SEX RATIO OF BLACK APPLE SNAIL (Pila polita Deshayes, 1830) IN MEKONG DELTA OF VIETNAM The black apple snail (Pila polita) is one of the snails (Ampullariidae) distributing in Mekong Delta, especially in the interior with high economic value. Study on the sex ratio of black apple snail distributed in some types of water bodies was conducted from November 2016 to October 2017 in some provinces of the Mekong Delta, Vietnam. A total of 3967 individuals in garden ditches, 1208 individuals in canals and 612 individuals in rice fields were collected for analysis. Gender identification was based on the external morphology and surgery through genital spenis, ovary and penis. Black apple snail specimen were distinguished, then separated into male and female. Male reproductive organs have vas deferens, penis, pouches containing sperm and sexual spines, genital spines. The female genitalia has genital holes, pallial oviduct, gonads and egg pouch and albumin glands. The sex ratio of the black apple snail in the garden ditches (1:1.24) was higher in irrigation canals (1:0.64) and the rice field (1:0.66). Percentage of male snails in the garden ditches was always lower than female snails and vice versa when distributed in irrigation canals and rice fields. The proportion of female snails increased with increasing size.